Pre-coagulated landfill leachate treatment by synergistic ultraviolet and electro-persulfate process - Can-Guven, Emine; Guvenc, Senem Yazici; Varank, Gamze; Demir, Ahmet (YILDIZ TECHNICAL UNIV, 2024)
In this study, the integration of ultraviolet (UV) and electrochemically activated persulfate (PS) oxidation (UV/Electro-PS) was investigated in pretreated landfill leachate treatment. Optimum process parameters for chemical oxygen demand (COD), UV254, and color removal from pre-coagulated landfill leachate were investigated. The process variables and ranges of variables were selected as pH 3-11, applied current 1-5 A, PS dose 1-9 g/L, and reaction time 5-35 min. Optimum process conditions were determined as pH 3, applied current 3 A, PS dose 5 g/L, and reaction time 25 min. By applying optimum conditions, COD, UV254, and color removal efficiencies by the UV/Electro-PS process were 55.6%, 68.5%, and 89.9%, respectively. The total energy consumption was calculated as 27.4 kWh/kg COD for the optimum process conditions. UV/Electro-PS process was effective for the COD, UV254, and color removal from pre-coagulated landfill leachate.
Keywords: Advanced Oxidation; COD; Color; Leachate; UV254; ADVANCED OXIDATION PROCESSES; HEAT-ACTIVATED PERSULFATE; INDUSTRIAL WASTE-WATER; ELECTROCHEMICAL ACTIVATION; HYDROXYL RADICALS; AQUEOUS-SOLUTION; COD REMOVAL; DEGRADATION; PRETREATMENT; SULFATE; Engineering